The Realization of Transitivity Systems in Undergraduate Learners’ Argumentative Essay Texts - Nurkholidah, Endang Siti; Sutopo, Djoko; Widhiyanto, Widhiyanto (Universitas Negeri Semarang, 2019)
Transitivity systems define as a system to explore how language concernes in the overall grammatical resources for construing going on. The ability to realize transitivity systems in argumentative essays is important because by realizing these systems, the writer can explore language in process of doing, sensing, saying activities happened in the real world. Therefore, this study aims to explore the realization of transitivity systems in students’ argumentative essay texts. There are five argumentative essays written by students who have a good quality in writing skill. The findings show that the writers have already realized six process types corresponding with participants and circumstances. By realizing all process types in essay, the readers can experience different world so that they will know the writers’ experience in using language to mark experiential meaning in essays. In this case, the writers mostly asked readers to experience with process of doing by material process. Thus, the writers moved the readers’ attention by showing the experience of stating relation of the participants. The relation was showed in a configuration of being in attributing and identifying the participants. Therefore, the occurrence of other processes as well as participants and circumstances makes the argumentative essay text more alive. Keywords: Transitivity Systems, Process types, Participants, Circumstances, argumentative essays.